PASANG SURUT PARADIGMA ADMINISTRASI PUBLIK - Anwaruddin, Awang (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2004)
In line with the change of government orientation by the end of twentieth century, from authority to democracy, the manner of public administration development tends to transform from theoretical to empirical. Accordingly, the preceding trademark of public administration as a compile of separate theories has to convert to be such a policy of Â Â problem solving to various public problems. The impact is the development of its dimensions towards the accomplishment of public needs, such as public management implementation, public policy, and public service functions (Nisjar, 1995:43-57).In fact, such consideration corresponds to the fundamental nature of public administration as initially formulated by Woodrow Wilson in 1887 (Frederickson, 1980:2).Â Afterward, for more than a hundred years the scholars of public administration have developed various theories and approaches to inductively analyze the thoughts on public administration. The impact is the dynamic development of models and paradigms of public administration varied after their devisers, and the continuous ambiguity of its definition and scopes (Tjokroamidjojo, 1987:16) as Nicholas Henry (1975:27) once said â€œ... there is a crisis of definition in the field of public administration.â€ Based on the analysis of various thoughts on public administration, this article aims at revealing Â such ambiguity confusing many students of public administration for years.